A Comparative Analysis Of Historical Thinking Skill Elements In Malaysian And Indonesian History Textbooks - Muhthar, Asmahani; Mahzan Awang, Mohd; Razaq Ahmad, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Malaysia and Indonesia have each made history textbooks an important medium in shaping the integration of knowledge, skills and values as well as shaping the country's history. Nevertheless, the basic concept of historical thinking is not much being emphasized in comparison to reflect the aspirations of the context of the two countries. Thus, this concept paper seeks to examine the comparative extent of the application of historical thinking skills in history textbooks in form 4 in Malaysia and Class 10 in Indonesia. Most of the literature is also seen as focusing more on historical thinking skills especially in teaching and learning aspects rather than looking at the application of teaching resources in particular by comparing the two countries. The idea behind this research is to discuss issues related to the implementation of historical thinking skills and to explore challenges in its implementation using history textbooks among students in Malaysia and Indonesia. In general, there is no denying that there are some similarities between the two countries in developing their historical thinking skills through textbooks. Positively, equality should be viewed in the interests of both countries. As global challenges continue to change, this comparison is seen important as an idea for cooperation between the two countries to generate greater historical integration through education.